Modeling of Sawdust Drying in Spouted Beds Using Solar Energy and Phase Change Materials - Reyes-Salinas, A; Henriquez-Vargas, L; Pailahueque-Barahona, N; Gatica-Candia, E (Elsevier Ltd, 2022)
In the present work, the modeling and simulation of the continuous drying of sawdust using spouted beds connected in series and a solar energy accumulator panel to heat the drying air was carried out. The modeling approach for the solar energy accumulator panel was based on energy balances, whereas for the dryer a combination of residence time distribution, drying kinetics and micro-mixing models was considered. Model parameters were adjusted with available experimental data. Simulations results were validated using experimental values, observing that the predicted outlet air temperature of the solar collector presented root mean squared errors lower than 1.9 °C for 5 different air flows, while the outlet sawdust moisture deviated less than 5.6%. Finally, the effect of increasing the number of spouted beds and the solids feed rate on the moisture content leaving the dryer was evaluated, showing a greater influence of the increase in spouted bed units compared to increasing the drying air temperature by 10 °C. © 2022 Elsevier Ltd